Winter precipitation effect in a mid-latitude temperature-limited environment: the case of common juniper at high elevation in the Alps - Elena Pellizzari; Mario Pividori; Marco Carrer (Environmental Research Letters, 2014)
Common juniper ( Juniperus communis L.) is by far the most widespread conifer in the world. However, tree-ring research dealing with this species is still scarce, mainly due to the difficulty in crossdating associated with the irregular stem shape with strip-bark growth form in older individuals and the high number of missing and wedging rings. Given that many different species of the same genus have been successfully used in tree-ring investigations and proved to be reliable climate proxies, this study aims to (i) test the possibility to successfully apply dendrochronological techniques on common juniper growing above the treeline and (ii) verify the climate sensitivity of the species with special regard to winter precipitation, a climatic factor that generally does not affect tree-ring growth in all Alpine high-elevation tree species. Almost 90 samples have been collected in three sites in the central and eastern Alps, all between 2100 and 2400 m in elevation. Despite cross-dating difficulties, we were able to build a reliable chronology for each site, each spanning over 200 years. Climate-growth relationships computed over the last century highlight that juniper growth is mainly controlled by the amount of winter precipitation. The high variability of the climate-growth associations among sites, corresponds well to the low spatial dependence of this meteorological factor. Fairly long chronologies and the presence of a significant precipitation signal open up the possibility to reconstruct past winter precipitation.